Quantification of Hair Follicles in the Scalp in Mexican Mestizo Population - Martínez Luna, Eduwiges (2018)
Introduction: There are no reports of the density of hair follicles in the scalp of Mexican mestizo population, necessitating the determination of normal references values for this population compared with other ethnic groups. Objective: To determine the average hair follicle count on the scalp in Mexican mestizo population. Materials and Methods: A total of 50 scalp samples (25 men and 25 women) from Mexican mestizo individuals aged between 19 and 60 years, with no clinical evidence of hair disease, obtained by biopsy punch at General Hospital “Dr. Manuel Gea González” were collected over 2 years. The total follicular density, vellus and terminal hair follicles, and the percentage in anagen and catagen-telogen phase were measured. χ2 was used as the basic statistical test. Results: The mean number of total hair follicles in our Mexican mestizo population was 23.2 ± 4.2, which is lower compared with Thais, Iranians, and Caucasians. However, the ratio of terminal and vellus hair follicles was higher than in Thais, Caucasians, and African-Americans. The percentage of terminal hairs in anagen phase was lower than in the other populations, and higher in telogen, without exceeding 15%, established as the normal reference value. There was an association between sex and terminal hairs in telogen phase (p < 0.05). The average follicular density per mm2 was slightly higher compared with AfricanAmericans and Asians. Women had more terminal hairs than men. Conclusions: The density of total follicles is lower in the Mexican mestizo population compared with Iranians, Thais, and Caucasians. However, the greater number of terminal hairs compared to vellus hairs gives the appearance of greater overall volume. The results of this study can be used as a reference for diseases of the scalp in the Mexican population.